2019
DOI: 10.4149/bll_2019_010
|View full text |Cite
|
Sign up to set email alerts
|

Vaspin, neutrophil gelatinase-associated lipocalin and apolipoprotein levels in patients with psoriatic arthritis

Abstract: OBJECTIVES: To examine the relationship between disease activity and vaspin, neutrophil gelatinase-associated lipocalin (NGAL) and apolipoprotein levels in patients with psoriatic arthritis (PsA). BACKGROUND: Psoriatic arthritis (PsA) is a chronic infl ammatory arthritis, which is related with psoriasis. Adipokines are the mediators which play a role in metabolic homeostasis and infl ammatory conditions. METHODS: The levels of vaspin, NGAL, apolipoproteins and their correlations with disease activity were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Conversely, chemerin levels were significantly lower in PsA patients compared to healthy controls. Also, vaspin systemic levels were found higher in PsA patients compared to healthy controls, even though there was no significant correlation with disease activity, measured using the disease activity in PsA (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Visual Analogue Scale (VAS), and Minimal Disease Activity (MDA) [100].…”
Section: Adipokines and Spamentioning
confidence: 88%
“…Conversely, chemerin levels were significantly lower in PsA patients compared to healthy controls. Also, vaspin systemic levels were found higher in PsA patients compared to healthy controls, even though there was no significant correlation with disease activity, measured using the disease activity in PsA (DAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Visual Analogue Scale (VAS), and Minimal Disease Activity (MDA) [100].…”
Section: Adipokines and Spamentioning
confidence: 88%
“…As a member of proinflammatory cytokines, it has been reported that IL-17 may be involved in the pathogenesis of psoriasis/PsA [2]. Some studies have demonstrated that IL-17 signaling pathways can induce LCN2 expression and secretion [8, 26]. Secretion of LCN2 can be regulated by IL-17 either alone or in conjunction with TNF- α [8, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that IL-17 signaling pathways can induce LCN2 expression and secretion [8, 26]. Secretion of LCN2 can be regulated by IL-17 either alone or in conjunction with TNF- α [8, 27]. It suggests that LCN2 might play an important role in potential psoriasis/PsA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemically, serum levels of vaspin were found to be higher in psoriatic arthritis (PsA) patients compared to healthy controls [245], whereas levels were lower in OA patients compared to healthy controls [239]. In synovial fluid, vaspin levels were significantly higher in RA compared to OA patients with a tendency to correlate with DAS28 in the RA group [246].…”
Section: Other Adipokines In Oa and Ramentioning
confidence: 99%